2018
DOI: 10.3390/rs10111752
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Coastal Upwelling in the South-Eastern Baltic Sea: Statistical Properties and Implications for the Coastal Environment

Abstract: A detailed study of wind-induced coastal upwelling (CU) in the south-eastern Baltic Sea is presented based on an analysis of multi-mission satellite data. Analysis of moderate resolution imaging spectroradiometer (MODIS) sea surface temperature (SST) maps acquired between April and September of 2000-2015 allowed for the identification of 69 CU events. The Ekman-based upwelling index (UI) was applied to evaluate the effectiveness of the satellite measurements for upwelling detection. It was found that satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…Tidal circulation is very low in the central part of the Laptev Sea and limitedly affects mixing at the study area [62,65]. Coastal upwelling events are commonly manifested by cold and turbid zones in satellite imagery in many world regions [95][96][97][98]. Distributions of sea surface temperature observed during coastal upwelling events show significant dependence on local bathymetry.…”
Section: Coastal Upwelling Near the Lena Delta In The Laptev Seamentioning
confidence: 94%
“…Tidal circulation is very low in the central part of the Laptev Sea and limitedly affects mixing at the study area [62,65]. Coastal upwelling events are commonly manifested by cold and turbid zones in satellite imagery in many world regions [95][96][97][98]. Distributions of sea surface temperature observed during coastal upwelling events show significant dependence on local bathymetry.…”
Section: Coastal Upwelling Near the Lena Delta In The Laptev Seamentioning
confidence: 94%
“…During wintertime, the Curonian Lagoon becomes famous for ice fishing, being, however, a dangerous leisure, since strong winds can break off the ice fields and drift them away from the shore together with the fishermen. With the changing climate resulting in warmer weather and more unstable ice cover, such incidents might increase in the future and require detailed information on the ice cover to plan rapid rescue missions.In the south-eastern Baltic (SEB), where the Curonian Lagoon (CL) is located, spaceborne SAR observations have been already used before to study the coastal upwelling and its environmental implications [24,25], monitoring of cyanobacteria blooms [26], and short-term mapping of ice conditions for planning potential zebra mussel farms [27]. However, the comprehensive use of spaceborne SAR data for detailed analysis of ice conditions in the Curonian Lagoon and the SEB is still lacking.…”
mentioning
confidence: 99%
“…In the south-eastern Baltic (SEB), where the Curonian Lagoon (CL) is located, spaceborne SAR observations have been already used before to study the coastal upwelling and its environmental implications [24,25], monitoring of cyanobacteria blooms [26], and short-term mapping of ice conditions for planning potential zebra mussel farms [27]. However, the comprehensive use of spaceborne SAR data for detailed analysis of ice conditions in the Curonian Lagoon and the SEB is still lacking.…”
mentioning
confidence: 99%
“…Studies carried out in the summer showed upwelling to be an important process affecting water mixing and coastal weather [4][5][6][7]. The upwelled water is usually nutrient-rich; therefore, upwelling affects primary production and the phytoplankton biomass [6,[8][9][10][11]. and frequency in winter.…”
Section: Introductionmentioning
confidence: 99%